Policy implications for promoting the adoption of electric vehicles: Do consumer’s knowledge, perceived risk and financial incentive policy matter? - Wang, Shanyong; Wang, Jing; Li, Jun; Wang, Jinpeng; Liang, Liang (Transportation research. Part A, Policy and practice, 2018)
Electric vehicles (EVs) have been regarded as one of the most promising green technologies to reduce carbon emissions and energy consumption from the transport sector. Understanding and exploring the factors that affect consumer’s intention to adopt EVs is important. The main purpose of this research is to analyze the effects of consumer’s knowledge about EVs, perceived risk, perceived usefulness and current financial incentive policies on consumer’s intention to adopt EVs using an extended technology acceptance model. The model is empirically tested using questionnaire survey data collected from 320 consumers in China. The results shown that consumer’s knowledge about EVs is positively and significantly related to perceived usefulness, attitude and intention to adopt EVs, but negatively and significantly related to perceived risk. Perceived risk negatively affects perceived usefulness, attitude and intention to adopt EVs. Meanwhile, perceived usefulness has a positive effect on adoption intention and attitude, and attitude is also positively related to the intention to adopt EVs. However, the results also indicate that the financial incentive policy has no significant effect on intention to adopt EVs. In addition, the results also find that consumers lacking of knowledge about EVs and perceiving high risk of EVs could be the psychological barriers to their acceptance of EVs. Based on the results, policy implications for increasing the adoption of EVs and suggestions for future research are discussed.